Differential tolerance of Trichoderma harzianum and Rhizoctonia solani towards silver nanoparticles: potential for agricultural applications? - HARTATI OKTARINA; TEUKU MUKHRIZA; LIDIJA ŠILLER; IAN SINGLETON (Universitas Syiah Kuala, 2022)
In the previous study, we examined the effect of silver nanoparticles (AgNPs) on beneficial soil fungus including Trichoderma harzianum (T22), and pathogenic soil-borne fungus, Rhizoctonia solani (AG3-PT). The result exhibited that T. harzianum (T22) is tolerance towards AgNPs. On the other hand, the pathogenic fungi, R.solani (AG3-PT), is more sensitive to AgNPs. T. harzianum is well known as biocontrol agent to suppress R. solani. Therefore, in this study we investigated the combination of T. harzianum (T22) and AgNPs at low concentration to control two strains of R. solani (AG3-PT and AG2-1). The effect of AgNPs at two different levels (20 mg L-1 and 50 mg L-1) was examined over the growth of the two strains of R. solani and T. harzianum (T22) using dual culture technique. The results shows that this combination have a potential to reduce colony growth of R. solani (AG2-1) at higher AgNPs concentration. However, it was not the case for R. solani (AG3-PT). It can be concluded that AgNPs toxicity depend on several factors including species strain and the size of AgNPs particle.